Human Health Risk Assessment and Management of Indian Population: An In-silico Approach - Poonam Sharma2, Rambir Singh1, A.B. Pant3, L.K. Dwivedi1* (Recent Research in Science and Technology, 2010)
Human health risk assessment and management (HHRAM) is a systemic approach to characterize the nature and concentration of human health risks associated with any health hazard and the possible restoration of health by utilizing the scientific and technological knowledge. Computer simulated work has been backbone in European countries for developing such approaches. Since not any synchronized HHRAM tool addressing to Indian population was available hence an in-silico approach allied to Indian circumstances was needed and so attempted to develop in present investigation. The study was completed in three phases; (1) HRA Questionnaire based data collection (2) Development of database and Database management system holding the data surveyed (3) Design and development of website uploaded with developed tool for risk communication and online health risk assessment & management. It is capable to reduce the health risks by identifying and characterizing the environmental, occupational and socio-economical health hazards exposing to human beings. The tool was developed with the help of advance computer software and programming languages viz. MySQL, Microsoft office 2007, Hypertext Preprocessor (PHP) and Cascading Style Sheets (CSS). Bio-calculators were also developed for statistical analysis of the data. Later the entire work was communicated worldwide through developed website named www.healthrisk.co.in for risk communication.